The urban system of the province of Tébessa between the reality of the commercial structure and the imperative of the last administrative organization - TOUMI, Fahmi; ALKAMA, Djamel (Journal of Human Sciences, 2020)
The study aims to discover the compatibility between the reality imposed by the commercial structure of the urban system of the province of Tébessa with the imperative of its last administrative organization fell under presidential decree 19-328 of December 8, 2019, creating the administrative districts in some wilayas, it was therefore necessary to submit the stores identified between 2017 and 2018 to spatial tests, and this demonstrated the compatibility between the commercial structure and the levels of administrative organization at the headquarters of the wilaya and the headquarters of the administrative districts and its imbalance at the level of departmental and municipal seats.